2007
DOI: 10.1103/physrevb.75.205202
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrogen motion in the Cu-H complex in ZnO

Abstract: The Cu-H complex in ZnO consists of Cu on Zn site and a hydrogen atom bound to a nearby O atom, with the O-H bond oriented in the basal plane of the hexagonal lattice to the c axis. The motion of hydrogen in the Cu-H complex is studied by the stress-induced dichroism. Stress applied at room temperature along ͓1210͔ results in an alignment of the Cu-H bond. The reorientation process was found to be thermally activated with the activation energy of 0.52± 0.04 eV. The connection of the hydrogen movement in the Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 37 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…Similar behavior was documented for a number of hydrogen-related complexes in ZnO and is normally explained by the difference in the zero-point energies of the O-H and O-D species. 12,17,39 The different annealing temperatures of XH and XD are, however, a new result. To get insight into the nature of XH, an annealing series for a ZnO sample treated in a mixture of H 2 and D 2 was also performed.…”
Section: G Thermal Stability Of Xhmentioning
confidence: 99%
“…Similar behavior was documented for a number of hydrogen-related complexes in ZnO and is normally explained by the difference in the zero-point energies of the O-H and O-D species. 12,17,39 The different annealing temperatures of XH and XD are, however, a new result. To get insight into the nature of XH, an annealing series for a ZnO sample treated in a mixture of H 2 and D 2 was also performed.…”
Section: G Thermal Stability Of Xhmentioning
confidence: 99%
“…These Cu þ acceptor ions are charge-compensated (i.e., passivated) by an adjacent OH À ion at an oxygen site. 36 The hydrogen can be "driven" from the Cu þ ions by heating a crystal in air to 900 C. This leaves isolated substitutional Cu þ ions that can then be converted to Cu 2þ ions with nearband-edge laser light when the temperature is below approximately 60 K. 8 The resulting substitutional Cu 2þ ions have a characteristic EPR spectrum that is easily monitored at temperatures near 6 K. 1,3,4 This production of Cu 2þ ions by removing the hydrogen at high temperature has been observed by Lavrov et al 9 in near-infrared-absorption experiments on hydrothermally grown ZnO crystals and has been computationally modeled by Hu and Pan. 37 A similar thermally induced dissociation behavior has been reported for nitrogen-hydrogen (N-H) complexes in ZnO crystals.…”
Section: Results From Electron Paramagnetic Resonancementioning
confidence: 97%
“…The results were linked to hydrogen diffusion, and it was suggested that the activation energy of hydrogen motion in ZnO is around 0.5 eV. 19 These results disagree with the early studies of hydrogen diffusion in ZnO. Mollwo 1 and Thomas and Lander 2 investigated hydrogen diffusion by detecting the change in conductivity of the ZnO samples.…”
Section: Hydrogen Moleculementioning
confidence: 87%
“…3 The different thermal stability of H BC and D BC we explain by different diffusion rates of the two isotope species, which comes from the difference in the zero-point energy of the O-H and O-D bonds. 19,20 In our model, H BC anneals out via diffusion and a subsequent trapping at some other defect. Provided H BC is dominant, the formation of a hydrogen molecule, H 2 , should be the main sink for isolated hydrogen.…”
Section: Bond-centered Hydrogenmentioning
confidence: 99%